2019
DOI: 10.1002/eco.2085
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variations of water use among riparian vegetation in tropical monsoon region of SW China

Abstract: Riparian vegetation is an important inhabitant of numerous forest ecosystems,although it is vulnerable and affected by the changes in climate or microclimate.Due to the fluctuation in rainfall and surface water availability, riparian plants usually exposed to two different seasons throughout the year: a dry season and a rainy season. However, water use patterns among riparian plants are still poorly understood in the tropical monsoon region. In this study, we used stable isotope techniques (δD and δ 18 O) coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
3
6
0
Order By: Relevance
“…In the floodplain habitat, the SWC of three soil layers were higher, and the water absorption layer of T. ramosissima was relatively shallow (Figure 7). This result is consistent with the results of a previous study in tropical monsoon region in which shallow soil was the main water source during the rainy season [51]. Li et al [22] also observed that the soil water content was relatively high and the dominant depth of plant water uptake was relatively shallow in the riparian zone of arid regions.…”
Section: Discussionsupporting
confidence: 92%
“…In the floodplain habitat, the SWC of three soil layers were higher, and the water absorption layer of T. ramosissima was relatively shallow (Figure 7). This result is consistent with the results of a previous study in tropical monsoon region in which shallow soil was the main water source during the rainy season [51]. Li et al [22] also observed that the soil water content was relatively high and the dominant depth of plant water uptake was relatively shallow in the riparian zone of arid regions.…”
Section: Discussionsupporting
confidence: 92%
“…CC BY 4.0 License. This finding has also been proven in riparian phreatophytic trees (Populus fremontii and Salix gooddingii) and riparian deep-rooted tree species (Busch et al, 1992;Bowling et al, 2017;Wang et al, 2019a). Even under shallow groundwater with high salinity, no river water was directly absorbed by riparian Eucalyptus coolabah alongside an ephemeral arid zone river in Australia (Costelloe et al, 2008).…”
Section: Introductionsupporting
confidence: 56%
“…These changes could profoundly affect the regional territorial and aquatic ecosystems and the water security of the BRB. First, the Buyuan River is an important source of water for certain tree species characterized by deep and extensive root systems occupying the BRB (Wang et al, 2019). The river also supports large areas of tea gardens and rubber plantations.…”
Section: Resultsmentioning
confidence: 99%